2016
DOI: 10.1096/fj.201500124rr
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary dyslexia candidate genes DYX1C1 and DCDC2 are regulated by Regulatory Factor X (RFX) transcription factors through X‐box promoter motifs

Abstract: DYX1C1, DCDC2, and KIAA0319 are three of the most replicated dyslexia candidate genes (DCGs). Recently, these DCGs were implicated in functions at the cilium. Here, we investigate the regulation of these DCGs by Regulatory Factor X transcription factors (RFX TFs), a gene family known for transcriptionally regulating ciliary genes. We identify conserved X-box motifs in the promoter regions of DYX1C1, DCDC2, and KIAA0319 and demonstrate their functionality, as well as the ability to recruit RFX TFs using reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 66 publications
1
30
0
Order By: Relevance
“…We confirmed the neuronal differentiation and ciliary gene STRT RNA-seq data with an independent method, qRT-PCR normalized against the housekeeping gene GAPDH. Pearson correlation coefficient plots demonstrated effectively identical differential gene expression patterns for a replication group of 17 genes ( Supplementary Figure S2; Supplementary Table S4 ): 4 neuronal differentiation markers (DCX, MAP2, TUBA1A, TUBB3); 2 cilia and ciliopathy genes (CCDC28B, IFT20); 6 cilia and ciliopathy genes with brain or neuron phenotypes (BBS1, BBS2, CC2D2A, IFT81, PDE6D, TCTN2); 2 candidate ciliogenic transcription factor genes (RFX2, RFX5); a ciliary dyslexia candidate gene (DYX1C1/DNAAF4); and 2 neuronal Parkinson’s disease associated genes (MAPT, SNCA) (Tammimies et al, 2016; Reiter and Leroux, 2017; Lauter et al, 2018; Youn and Han, 2018). Ciliogenesis was thus found as a prominent aspect during LUHMES neuronal differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…We confirmed the neuronal differentiation and ciliary gene STRT RNA-seq data with an independent method, qRT-PCR normalized against the housekeeping gene GAPDH. Pearson correlation coefficient plots demonstrated effectively identical differential gene expression patterns for a replication group of 17 genes ( Supplementary Figure S2; Supplementary Table S4 ): 4 neuronal differentiation markers (DCX, MAP2, TUBA1A, TUBB3); 2 cilia and ciliopathy genes (CCDC28B, IFT20); 6 cilia and ciliopathy genes with brain or neuron phenotypes (BBS1, BBS2, CC2D2A, IFT81, PDE6D, TCTN2); 2 candidate ciliogenic transcription factor genes (RFX2, RFX5); a ciliary dyslexia candidate gene (DYX1C1/DNAAF4); and 2 neuronal Parkinson’s disease associated genes (MAPT, SNCA) (Tammimies et al, 2016; Reiter and Leroux, 2017; Lauter et al, 2018; Youn and Han, 2018). Ciliogenesis was thus found as a prominent aspect during LUHMES neuronal differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining candidate genes for SRD have received relatively little attention in human neuroimaging studies. Like those of other SRD candidate genes, the protein encoded by DYX1C1 has been linked to neurodevelopmental processes (Currier, Etchegaray, Haight, Galaburda, & Rosen, ; Rosen et al, ; Szalkowski et al, ; Tammimies et al, ; Tarkar et al, ; Threlkeld et al, ; Wang et al, ), and variation on this gene has been associated with reading and spelling abilities in both general population (Bates et al, ; Newbury et al, ; Zhang et al, ) and clinical samples (Lim, Ho, Chou, & Waye, ; Marino et al, ; Venkatesh, Siddaiah, Padakannaya, & Ramachandra, ). With respect to neuroimaging, Darki et al () found a relationship between SNP rs3743204 in DYX1C1 and white matter volume in bilateral temporo‐parietal regions and correlations between white matter volume in these regions and reading scores.…”
Section: Specific Reading Disabilitymentioning
confidence: 99%
“…We did not find any other structural variants in regions overlapping with candidate genes. 12 In summary, in individual 2 we identified a common DD-associated haplotype and a rare variant of unknown significance in the outer dynein arm component DNAH11, both inherited from the mother. 13…”
Section: Dyx1c1mentioning
confidence: 87%
“…Several reports have demonstrated that DD candidate genes have a role in cilia (7,8,11,12,(14)(15)(16)(17)(18). Furthermore, L/R asymmetry defects in the brain have been proposed as an anatomical basis to neurodevelopmental disorders such as schizophrenia and specifically to DD, possibly mediated by ciliary dysfunction (13,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation